Asphaltenes as model compounds of the UIBs/AIBs detected in various astrophysical objects. Part 2 – Natural bitumens asphaltenes carbonization. Issue 7 (3rd July 2022) - Cataldo, Franco; García-Hernández, D. Aníbal; Manchado, Arturo
Abstract: A series of naturally occurring bitumen samples from Central-South Italy (Maiella and Rivello) as well as from Sicily (Ragusa and Modica area), were purified and analyzed by thermal analysis (TGA-DTG-DTA) and FT-IR spectroscopy. The asphaltene fraction of these bitumen samples was isolated and analyzed by thermal analysis and by FT-IR spectroscopy. Each asphaltene fraction was then subjected to carbonization in a sealed crucible using a DSC scan to 700 °C under N2 flow and the carbonization product was studied by FT-IR spectroscopy. The naturally occurring bitumen samples, their asphaltenes and the carbonization products were used as model compounds to match the UIBs/AIBs (Unidentified Infrared Bands or Aromatic Infrared Bands) band pattern of the interstellar medium and their evolution in different interstellar and circumstellar environments. The asphaltenes extracted from the bitumen samples represent a concrete example of model compounds for the MAONs (mixed aromatic/aliphatic organic nanoparticles) theorized as the most probable carriers of the UIBs/AIBs.